2010
DOI: 10.1590/s0102-86502010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification by computerized morphometry of tissue levels of sulfomucins and sialomucins in diversion colitis in rats

Abstract: PURPOSE: To quantify the intensity of sulfomucin and sialomucin expression in the colon mucosa, by means of computer-assisted image processing, comparing segments with and without fecal stream and correlating with the duration of fecal transit exclusion. METHODS: Forty-five Wistar rats were subjected to diversion of the fecal stream in the left colon by means of constructing a proximal colostomy and distal mucosal fistula. They were distributed randomly into three experimental groups of 15 animals, of which 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 33 publications
3
66
0
7
Order By: Relevance
“…Glotzer et al 1 The mucous layer covering the colon epithelium is the first line of defense against invasion of the intestinal wall by bacteria and antigen that are present in the intestinal lumen 4,5 . Most of the protective effect provided by the mucous layer relates to the presence of mucins, which are the predominant glycoproteins in the chemical composition of colonic mucous [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Glotzer et al 1 The mucous layer covering the colon epithelium is the first line of defense against invasion of the intestinal wall by bacteria and antigen that are present in the intestinal lumen 4,5 . Most of the protective effect provided by the mucous layer relates to the presence of mucins, which are the predominant glycoproteins in the chemical composition of colonic mucous [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of the colonic epithelium to produce mucins depends on adequate supply of SCFAs 7 . Recent studies have shown the importance of maintaining the supply of SCFAs, particularly butyrate, in order to have adequate gene expression relating to mucin formation and content of the glycoprotein 4,5,8,13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting oxidative stress causes histological and biochemical alterations similar to those found in experimental models of chemically induced colitis or human colitis. The oxidative stress causes alterations in the colonic mucosa that aggravate according to the time of diversion [20][21][22][23][24][25][26][27] . Based on these evidences, the use of substances with antioxidant activity was suggested to be effective in the prevention and treatment of this disease 20,27 .The benefits of these substances in the treatment of DC were recently confirmed with the application of enemas with 5-aminosalicylic acid (5-ASA), a powerful antioxidant, was demonstrated to reduce the levels of tissue oxidative stress and improve the inflammatory process in the mucosa without fecal stream, even after the ex-vivo exposure to hydrogen peroxide (H 2 O 2 ) 27 .…”
Section: Introductionmentioning
confidence: 99%